Effects of stable and fluctuating soil water on the agronomic and biological performance of root vegetables - Li, Ge; Zhu, Guolong; Liu, Jian; Wang, Zhuan; Long, Huaiyu; Zhang, Renlian; Yu, Kefan (Frontiers in Plant Science, 2024)
Compared to fluctuating soil water (FW) conditions, stable soil water (SW) can increase plant water use efficiency (WUE) and improve crop growth and aboveground yield. It is unknown, however, how stable and fluctuating soil water affect root vegetables. Here, the effects of SW and FW were studied on cherry radish in a pot experiment, using negative pressure irrigation and conventional irrigation, respectively. The assessed effects included agronomic parameters, physiological indices, yield, quality and WUE of cherry radish. Results showed that under similarly average soil water contents, compared with FW, SW increased plant photosynthetic rate, stomatal conductance and transpiration rate, decreased leaf proline content by 13.7-73.3% and malondialdehyde content by 12.5-40.0%, and increased soluble sugars content by 6.3-22.1%. Cherry radish had greater biomass accumulation and nutrient uptake in SW than in FW. Indeed, SW increased radish output by 34.6-94.1% with no influence on root/shoot ratio or root quality. In conclusion, soil water stability affected directly the water physiological indicators of cherry radish and indirectly its agronomic attributes and nutrient uptake, which in turn influenced the crop biomass and yield, as well as WUE. This study provides a new perspective for improving agronomy of root crops and WUE through managing soil water stability.